Nilai Tradisi Lisan Tutur Adat Takanab untuk Pembentukan Karakter Anak Melalui Layanan Bimbingan dan Konseling - Banu, Edigius Paulus; Lio, Stefanus; Bone, Matilda Pia (Universitas Mathla'ul Anwar Banten, 2024)
This research aims to understand the essence of local wisdom values in the oral tradition of Takanab traditional speech with a focus on efforts to shape children's character through guidance and counseling services. The method applied in this research is a qualitative descriptive method, with the research subjects being traditional elders who have a deep understanding of the Takanab traditional spoken language. The data collection approach includes semi-structured interviews, observation, and documentation studies. Data analysis is carried out by data reduction, data display, and data verification. The research results show that the oral tradition of Takanab traditional speech includes moral, religious and cultural values that are significant in forming children's character. The research results concluded that in Takanab traditional speech there are values such as honesty, integrity, compassion, justice, responsibility, devotion, forgiveness, tolerance, courtesy, humility, respect, appreciation, hearing, recognition, empathy, sympathy, and discipline. These values can be the basis for forming children's character through information services, group guidance, group counseling and individual counseling in the implementation of guidance and counseling services. An oral tradition-based guidance and counseling approach emphasizes the importance of knowledge transmitted through stories, myths and oral experiences from generation to generation. Traditional narratives are used to provide views on life, values, and solutions to problems faced by individuals. This approach views oral traditions as a source of wisdom that can provide deep insight and help individuals understand the meaning of life in a cultural context and the values rooted in oral traditions are the basis for character formation.